Life as We Know It - Seckbach, Joseph (Cellular Origin, Life in Extreme Habitats and Astrobiology, 2006)
Life As we Know It ["LAKI"] covers several aspects of Life, ranging from the prebiotic level, origin of life, evolution of prokaryotes to eukaryotes and finally to various affairs of human beings. Although it is hard to define Life, one can, however, characterize it and describe its features. Topics treated are categories of bacteria, algae and fungi, conscience, philosophy, theology, aesthetics, appearance of sport and life destiny, life after clinical death, and thoughts of the world to come ("Olam Haba"). The various chapters have been written so that they are accessible to all - from the avid lay reader to the specialist - and make available multidisciplinary sources of information about Life. This volume will interest open minded scholars, students at all levels of general sciences, natural and Life science, researchers of philosophy, theology, history of Life, astrobiology, and those who wish to widen their knowledge about "who are we in the universe". The information presented here on the various phenomena of Life were all written by highly qualified authors including scientists, public leaders, a professional athelete and three Nobel Laureates.